Transperineal aggressive angiomyxoma - Pereira, Pedro (2017)
A 45-year-old woman with a history of total hysterectomy with adnexal preservation for uterine leiomyomas presented to our hospital with a right gluteal palpable mass, which she first noticed 6 months before and had progressively enlarged since then. Radiological studies revealed a 14 cm lesion with translevator growth that displaced rather than invaded adjacent structures, with a peculiar whorled pattern on T2-weighted MRI, which enhanced following gadolinium administration. CT-guided biopsy was performed, and in conjunction with imaging features the diagnosis of an aggressive angiomyxoma was assumed and confirmed following surgical excision.